Relapses of Anti-NMDAR, Anti-GABABR and Anti-LGI1 Encephalitis: A Retrospective Cohort Study - Zhong, Rui; Chen, Qingling; Zhang, Xinyue; Zhang, Hanyu; Lin, Weihong (Frontiers in Immunology, 2022)
Abstract Objective: To investigate the relapse rate and study the factors that may predict the subsequent relapse in anti-NMDAR, anti-GABABR and anti-LGI1 encephalitis in Northeast China. Methods: In the retrospective cohort study, we consecutively enrolled patients with anti-NMDAR, anti-GABABR and anti-LGI1 encephalitis between March 2015 and November 2021. The patients were followed up for at least 6 months. The outcome variable was a binary variable of relapse or not. Predictors of relapse were identified. Results: A total of 100 patients were enrolled. Relapse occurred in 26 (26%) patients after a median follow-up of 18 months since the first event. The relapse rates of anti - NMDAR, anti - GABABR and anti - LGI1 encephalitis were 25%, 33.3%, and 28.6%, respectively. The multivariable analysis results suggested that immunotherapy delay at the acute phase was independently associated with an increased risk of relapse in total patients (HR = 2.447, 95% CI = 1.027 - 5.832; P = 0.043). Subgroup analysis results showed that antibody titer was associated with the likelihood of relapse in anti-LGI1 encephalitis. The higher the concentration, the more likely it was for patients to have relapse (p=0.019). Conclusion: The general relapse rate of anti-NMDAR, anti-GABABR and anti-LGI1 encephalitis was 26%. The risk of subsequent relapse was elevated in those with delayed immunotherapy in the first episode. In subgroup of anti-LGI1 encephalitis, higher antibody titer was the risk factors of relapse. Thus, timely and aggressive immunotherapy may be beneficial for patients to prevent subsequent relapse.